Selected writings on race and difference - Hall, Stuart, 1932-2014 (Hall, Stuart, 1932-2014. Works. 2016., 2021)
"Selected Writings on Race and Difference gathers more than twenty essays by Stuart Hall that highlight his extensive and groundbreaking engagement with race, representation, identity, difference, and diaspora."--